Entomofauna associada às sementes de canela-guaicá [Ocotea puberula (Reich.) Nees] e louro-pardo [Cordia trichotoma (Vell.) Arrab. ex Steud.] - Fleck, Marciane Danniela (2018)
Forest species may have their seeds damaged by granivorous insects, especially in the larval stage. The larvae feeding on the embryo and the reserve of the seeds sometimes prevent germination. Thus, studies related to the entomofauna associated with fruits and seeds, besides reporting the occurrence of these insects and their natural enemies, also indicate their potential risk of pest. In this context, the objective of the present work is to determine the granivorous insects species associated with the seeds of the forest species canela-guaicá (Lauraceae) and louro-pardo (Boraginaceae) as well as verify the occurrence of parasitoid species (Hymenoptera). The specific objectives were to qualify and quantify the damage caused by granivorous insects in stored fruits, to evaluate the presence and interference of larvae in seed germination at different maturation periods, and to compare the germination and the occurrence of insects in seeds with and without evidence of damage. For that, seven trees for each forest species were selected in the city of Taquaruçu do Sul, RS. Fruit collection was performed weekly in the middle third of the canopy, from the beginning of the formation of the fruits until the total dehiscence. For the species O. puberula, from the lot, 100 fruits per collection were sectioned with the aid of a scalpel and binocular magnifying glass in order to verify the percentage of damaged fruits. These fruits were classified as: a) healthy (with normal appearance, free from insect damage); b) with damages (presence of holes or galleries); c) with an insect or an indication of its presence (egg, larva, pupa and adult of insect or parasitoid) and d) empty seeds and/or without embryos (unnatural formation). Likewise, 144 fruits, packed in six 24-well plates, were stored individually to determine the granivorous insects. After the emergence of the adult insects, these fruits were sectioned to verify the damages and their separation in intact and damaged, to obtain the percentage of consumption by the larvae. For the species C. trichotoma, the procedures of sectioning and individualization of the fruits were performed by tree and not from the lot, being 15 and 10 fruits, by tree/collect, respectively. The verification of the damage caused to the seeds was carried out with germination test, with four replicates of 25 seeds, comparing the intact and damaged seeds. In general, the results allow us to conclude that Heilipus draco (Fabricius) and Conotrachelus spp. (Coleoptera: Curculionidae) are the species of granivorous insects that cause damages to the seeds of O. puberula, with endophytic postures carried out directly in the seed. The larvae of these species consume the embryo and the seed reserve, resulting in a decrease in the number of normal seedlings in the germination test. The larvae of the Curculionidae are parasitized by Hymenoptera of the genus Bracon, Dirrhope, Omeganastatus e Scambus. For C. trichotoma the insects associated with the fruits are Amblycerus longesuturalis (Pic) e Amblycerus profaupar Ribeiro-Costa (Chrysomelidae: Bruchinae) where the postures are held predominantly between the calyx and the top of the fruit, and the larvae need pierce the fruit to feed. Bruchinae larvae are parasitized by Hymenoptera of the genus Bracon, Dirrhope, Mirax e Omeganastatus. In both forest species, the infestation rate of the granivorous insects is differentiated between the fruiting years, as well as, during the maturation of the fruits, and the seeds with indications of the presence of granivorous insects have significantly impaired germination.